Tau phosphorylation sites work in concert to promote neurotoxicity in vivo. - Steinhilb, M; Dias-Santagata, D; Fulga, T; Felch, D; Feany, M (2007)
Tau is a microtubule binding protein implicated in a number of human neurodegenerative disorders, including Alzheimer's disease. Phosphorylation of serine-proline/threonine-proline sites, targeted by proline-directed kinases, coincides temporally with neurodegeneration in the human diseases. Recently, we demonstrated that this unique group of serines and threonines has a critical role in controlling tau toxicity in a Drosophila model of tauopathy. Here, we use a combination of genetic and biochemical approaches to examine these sites individually and to determine which of them is primarily responsible for controlling tau neurotoxicity. Despite the importance placed on individual phosphoepitopes and their contributions to disease pathogenesis, our results indicate that no single phosphorylation residue plays a dominant role in controlling tau toxicity. These findings suggest that serine-proline/threonine-proline sites cooperate to mediate neurodegeneration in vivo.